Embodying forgiveness a theological analysis - Jones, L. Gregory (Grand Rapids, MI Eerdmans, 1995)
Includes bibliographical references and index.
Keywords: Forgiveness -- religious aspects -- Christianity; Reconciliation -- religious aspects -- Christianity